Pengaruh Citra Merek, Persepsi Harga, Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Sicepat Ekspres Jakarta - Lutfiyah Maharrani; Rully Arifiansyah (Human Capital Development, 2022)
The purpose of this study is to investigate how the customer satisfaction of Sicepat Ekspres Jakarta is affected by factors such as the perception of the pricing of services and the quality of those services. In this study, a purposive sampling approach was taken, and the total number of participants who served as research samples was one hundred. A questionnaire was used to collect the data for this study. The primary data from the subsequent investigation were evaluated using multiple linear regression test instruments within SPSS 25. According to the findings of this research project, factors such as customer happiness are partially influenced by brand image, price perception, and service quality. Furthermore, when taken as a whole, the analysis findings explain why factors such as customer happiness are related to brand image, price perception, and service quality. Keywords : Brand Image; Price Perception; Service Quality; Customer Satisfaction